Keeping Education Non-Confessional While Teaching Children about Religion. Issue 3 (3rd July 2019) - Puskás, Tünde; Andersson, Anita
Abstract: The paper explores how in a Swedish preschool with a religious profile teachers balance between keeping education non-confessional and teaching about a tradition with religious roots. In this paper, the focus is on how and why the secular and religious narratives are intertwined in a play that aims to teach children about why Easter is celebrated. Theoretically we combine Grimmitt's theoretical concepts of learning about and learning from religion with Smart's analytical framework. The analysis reveals that through translating between the secular and religious narratives the play offered an opportunity to learn both about and from religion.